Optimizing the selection of a biometric template from a sequence - Gneushev, A. N.; Kovkov, D. V.; Matveev, I. A.; Novik, V. P. (Journal of computer & systems sciences international, 2015)
The problem of choosing the best biometric template from a group constructed based on a sequence of registered images is addressed. A method based on the analysis of the matrix of distances of a group of templates is proposed. A comparison with the standard approaches using the quality indices of the initial image is performed. It is specified that the quality indices of the image are developed for the problem of rejecting poor images and little suit the problem of choosing the best image. The computer experiments were conducted based on several databases available in open source with more than 70000 images. The tests have shown that the proposed method provides a slightly better quality of the chosen templates. Note that the method does not require the development of additional quality measures and employs the calculations of the distance available.